Efektif Pemeriksaan CT-Scan Kepala Non-Kontras Berdasarkan Gender Dengan Menggunakan Kalkulator Dosis Radiasi Di RS Hermina Bitung - Darmawan, Ifan Aji; Juliantara, I Putu Eka; Adi, Langkir Sapto; Astien, Astien; Wahab, Revalita (Fakultas Kedokteran Universitas Trisakti, 2024)
Background The need for CT Scan radiology examinations, which offer more detailed image results than X-rays, continues to increase. Head CT scans are the most frequently performed examinations, reaching 60%. Objective This study aims to evaluate the effective dose distribution of radiation to the tissues involved in head CT-Scan examinations at RS Hermina Bitung and assess its compliance with the regulations set by the Indonesia Diagnostic Reference Level (I-DRL). Methods This study involved 100 patients, consisting of 50 men and 50 women. Data in the form of Dose Length Product (DLP) values were collected from each patient and converted to effective dose using a radiation dose calculator. Results The results showed that 6 out of 100 samples exceeded the dose limit set by the Nuclear Energy Regulatory Agency (BAPETEN). Factors that affect the effective dose include exposure, body weight, object thickness, scan length, age, tissue weight, tissue sensitivity, FOV, and pitch. Nonetheless, the overall average effective dose of the patients was still within the I-DRL. Conclusions Factor such as gender can affect the effective dose received by patients. The 75 percentile value of the effective dose of non-contrast head CT-Scan examination at Hermina Bitung Hospital is in accordance with the provisions of the I-DRL. The radiation dose calculator used can be applied in Indonesia, but still requires increased information literacy regarding its use.